A Pedagogia Histórico-Crítica como fundamento de algumas iniciativas de formação continuada de professores e professoras da Educação Básica no Brasil. - Lopes, Silmara Aparecida (Universidade Federal de São Carlos, 2023)
The objective of the research was to analyze and discuss the limits and possibilities of some initiatives for the continuing education of teachers in Basic Education in Brazil, based on the PHC and investigated in this work, developed with different formats: study and/or research groups; short courses (up to 40 hours); medium-term courses (from 50 to 100 hours); long-term courses (more than 100 hours); undergraduate subjects; graduate courses; speeches; seminars; self-managed study groups; among others, based on Historical-Critical Pedagogy (PHC). The method of collecting and analyzing sources and data in this research is historical-dialectical materialism (MHD). To carry out the research, the following procedures were selected: bibliographic review; document and field analysis. It is argued that some initiatives for continuing education of Brazilian Basic Education teachers, investigated in this work, based on PHC, currently face limits and possibilities. One of the limits refers to the concrete conditions in which the performance and training of teachers of Basic Education in Brazil take place. However, despite the objective and subjective conditions that involve Brazilian education as a whole, which have repercussions on teacher education, it is possible and necessary to build initiatives for the continuing education of teachers, based on the PHC, which are increasingly stronger, articulated, with a more systematized organization and supported by collective movements at the national level and with common objectives. Such initiatives are fundamental possibilities as forms of resistance and struggle, which aim to contribute to the struggles in favor of transforming the school and society itself.
Historical-Critical Pedagogy. Training of Basic Education Teachers. Dermeval Saviani.
Keywords: Pedagogia Histórico-Crítica; Formação de professores da educação básica; Dermeval Saviani; Historical-Critical Pedagogy; Training of basic education teachers; CIENCIAS HUMANAS::EDUCACAO